Pertussis Toxin Up-regulates Angiotensin Type 1 Receptors through Toll-like Receptor 4-mediated Rac Activation - Nishida, Motohiro (American Society for Biochemistry and Molecular Biology, 2010)
Pertussis toxin (PTX) is recognized as a specific tool that uncouples receptors from G(i) and G(o) through ADP-ribosylation. During the study analyzing the effects of PTX on Ang II type 1 receptor (AT1R) function in cardiac fibroblasts, we found that PTX increases the number of AT1Rs and enhances AT1R-mediated response. Microarray analysis revealed that PTX increases the induction of interleukin (IL)-1β among cytokines. Inhibition of IL-1β suppressed the enhancement of AT1R-mediated response by PTX. PTX increased the expression of IL-1β and AT1R through NF-κB, and a small GTP-binding protein, Rac, mediated PTX-induced NF-κB activation through NADPH oxidase-dependent production of reactive oxygen species. PTX induced biphasic increases in Rac activity, and the Rac activation in a late but not an early phase was suppressed by IL-1β siRNA, suggesting that IL-1β-induced Rac activation contributes to the amplification of Rac-dependent signaling induced by PTX. Furthermore, inhibition of TLR4 (Toll-like receptor 4) abolished PTX-induced Rac activation and enhancement of AT1R function. However, ADP-ribosylation of G(i)/G(o) by PTX was not affected by inhibition of TLR4. Thus, PTX binds to two receptors; one is TLR4, which activates Rac, and another is the binding site that is required for ADP-ribosylation of G(i)/G(o).